Effects of Steam Explosion Pretreatment (SEP) On Natural Fibers: A Review - Darus, Siti Atiqa Al Zahra Binti Mat; Ghazali, Mariyam Jameelah; Azhari, Che Husna Che; Zulkifli, Rozli; Mustafa, Mohd Tamizi; Sarac, Hanifi (MALAYSIAN TRIBOLOGY SOC-MYTRIBOS, 2016)
Surface treatment on natural fibers is normally performed to enhance the workability and compatability between the matrix-fibers in composites. This paper presents a review of a steam explosion pretreatment (SEP) on natural fibers for natural composites. The review emphasized on the optimum parameters of the SE (steam explosion) method, chemical composition, morphology and the produced fiber size along with the mechanical properties of the produced composites. In short, the SEP is an effective method in obtaining 10(-6) to 10(-9) m (meso-scaled) sized BF (bamboo fibers) for high quality natural fiber composites.
Keywords: Natural Fiber; Steam Explosion; morphology; BAMBOO CELLULOSE FIBERS; MECHANICAL-PROPERTIES; COMPOSITES; Engineering